Utilization of distiller’s dried grains with solubles in swine diets - Williams, Scott Matthew (Kansas State University, 2010)
Six experiments were completed to determine factors influencing the use of distillers dried grains with solubles (DDGS) in diets for nursery and finishing pigs. In Exp. 1, 105 nursery pigs were fed corn-soybean meal (SBM) based diets with CP concentrations of 22.5, 25, and 27.5%. Overall ADG, ADFI, and G:F were not affected by increasing CP (P > 0.19). In Exp. 2, 105 nursery pigs were fed excess CP from SBM and DDGS. Overall ADG, ADFI, and G:F for pigs fed the control diet were not different from those fed the high CP treatments (P > 0.12). However, pigs fed the DDGS treatment had lower G:F than pigs fed the corn-soy diet with similar CP content (P < 0.04). For Exp. 3, 176 finishing pigs were fed diets with CP concentrations increasing from 12 to 18%. Increasing CP had no effect (P > 0.20) on ADG, ADFI, G:F, and hot carcass weight (HCW). For Exp. 4, 180 finishing pigs were fed excess dietary CP from SBM and DDGS. Pigs fed diets with high CP had lower ADG, ADFI, and HCW, but these results were caused by the diet with 40% DDGS (SBM vs DDGS, P < 0.001). For Exp. 5, 224 nursery pigs were used to determine the effects of extrusion processing on the nutritional value of DDGS. Overall ADG and ADFI were greater for pigs fed the corn-soy control compared to the DDGS treatments (P < 0.02). Extruding the DDGS did not improve ADG or G:F (P > 0.11), but DM and GE digestibility were greater for diets with extruded DDGS vs. unprocessed DDGS (P < 0.04). In Exp. 6, 200 finishing pigs were fed DDGS-based diets formulated for ME, NE, and digestible amino acids. Feeding DDGS lowered ADG (P < 0.09) and ADFI (P < 0.05). Formulating for ME, NE, and digestible amino acids needs improved ADG and G:F (P < 0.002) to that of the corn-soy control diet. In conclusion, moderate excesses of dietary CP does not impact growth performance. Also, extruding DDGS can improve the nutritional value of diets for nursery pig and formulating for ME, NE and digestible amino acid needs can improve growth performance of finishing pigs fed diets with high levels of DDGS.
Keywords: Excess dietary crude protein; DDGS; Extrusion; digestible amino acids; nursery and finishing pigs; Agriculture, Animal Culture and Nutrition (0475)